A novel APC mutation defines a second locus for Cenani–Lenz syndrome. Issue 5 (12th February 2015) - Patel, Nisha; Faqeih, Eissa; Anazi, Shams; Alfawareh, Mohammad; Wakil, Salma M; Colak, Dilek; Alkuraya, Fowzan S
Abstract : Background: Cenani–Lenz syndrome (CLS) is an autosomal recessive condition characterised by a unique pattern of syndactyly, and variable penetrance of renal agenesis and facial dysmorphism. LRP4 mutations were identified in most, but not all patients with this syndrome, suggesting the presence of at least one additional locus. Materials and methods: Clinical characterisation of a new CLS family followed by autozygosity mapping, whole-exome sequencing and global gene expression profiling. Results: We describe an extended consanguineous Saudi family with typical CLS features in addition to significant scoliosis. The disease in this family maps to a single autozygous interval on 5q22.2, in which whole-exome sequencing revealed the presence of a novel splicing mutation in APC that results in ∼80% reduction of the wild-type transcript and the creation of an aberrant transcript that predicts a severely truncated APC . This was found to be associated with upregulation of Wnt/β-catenin signalling. Conclusions: In a pattern similar to how LRP4 mutations are predicted to negate the protein's antagonistic effect on Wnt/β-catenin signalling, we propose that reduction of APC may increase the availability of β-catenin by virtue of impaired degradation, leading to a similar phenotypic outcome. This is the first time APC is linked to a human phenotype distinct from its established role in oncology.